2018
DOI: 10.36104/amc.2018.1074
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización clínica y microbiológica de la bacteriemia por Staphylococcus aureus

Abstract: Introducción: Staphylococcus aureus es una frecuente causa de bacteriemias y el incremento en las tasas de resistencia dificulta su tratamiento inicial. La incidencia de bacteriemias por S. aureus resistente a meticilina (SAMR) ha aumentado, principalmente en las infecciones adquiridas en el medio hospitalario. Este estudio pretende caracterizar clínicamente a los pacientes con bacteriemia por S. aureus detectados en un hospital de Medellín y definir su perfil de resistencia microbiana. Métodos: cohorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Local studies have reported a mortality due to SA of 24-30% [ 3 ]. In a study conducted at the San Vicente Fundación Hospital of Medellin, SA bacteremias cases were collected retrospectively for 4 years (2012-2016) the results showed 43% of those infected were in RRT [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Local studies have reported a mortality due to SA of 24-30% [ 3 ]. In a study conducted at the San Vicente Fundación Hospital of Medellin, SA bacteremias cases were collected retrospectively for 4 years (2012-2016) the results showed 43% of those infected were in RRT [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vancomycin is the drug of choice for the treatment of MRSA bacteremia [ 2 ]. This antibiotic has a narrow therapeutic margin, and inadequate dosage poses a risk of toxicity [ 4 ] while underdosing predisposes to therapeutic failure and emergence of resistant microorganisms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1). In patients with CKD-HD, bacteremia due to SA presents high morbidity, mortality and increased risk of MRSA (2). Local studies have reported a mortality due to SA of 24-30% (3).…”
Section: Introductionmentioning
confidence: 99%
“…Vancomycin is the drug of choice for the treatment of MRSA bacteremia (2). This antibiotic has a narrow therapeutic margin and inadequate dosage generates risk of toxicity (4) while underdosing predisposes to therapeutic failure and emergence of resistant microorganisms (5).…”
Section: Introductionmentioning
confidence: 99%